1969
DOI: 10.1111/j.1365-2621.1969.tb12785.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Bovine Natural Actomyosin 1. Relationship of ATPase and Contractility to Tenderness of Muscle

Abstract: The effects of muscle tenderness classification and of aging muscle postmortem on ATPase activity and superprecipitation of natural actomyosin were studied. Actomyosin from muscle 12-and 24-hr postmortem had higher ATPase activity than that from 0-hr, 5-day aged or IO-day aged muscle. However, ATPase activity did not usually return to the 0-hr level. No consistent differences were found in actomyosin ATPase activity after the various periods of aging for actomyosins from tough and tender muscle. Superprecipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1969
1969
2004
2004

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…The muscle source (longissimus) and sampling procedures were similar to those described previously (Herring et al, 1969b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscle source (longissimus) and sampling procedures were similar to those described previously (Herring et al, 1969b).…”
Section: Methodsmentioning
confidence: 99%
“…Maruyama et al (1965) and Briskey et al (1967) observed that cu-actinin promoted gelation of actomyosin with possibly more cross-linking of the actin moiety resulting in the formation of a ternary complex in actomyosin. Herring et al (1969b) observed that tender and tough muscle differed in properties of superprecipitation and they suggested a higher content BOVINE NATURAL ACTOMYOSIN.…”
Section: Effect Of Tenderness Classification On Reduced Viscositymentioning
confidence: 99%
“…Actomyosin obtained without ATP was regarded as an analog of "Natural" actomyosin Journal of Zhejiang University SCIENCE ISSN 1009-3095 http://www.zju.edu.cn/jzus E-mail: jzus@zju.edu.cn (AMN). AMN from PSE and normal pork were prepared by a modification of the methods used by Herring et al(1969) and Karlsson et al(1999). Twenty-five grams muscle was homogenized in chilled 100 ml 50 mmol/L phosphate buffer (pH 7.5) at 1500 rev/min for 3 min.…”
Section: Extraction and Purification Of Actomyosinmentioning
confidence: 99%
“…ATPásica miofibrilar en función de la velocidad de congelación expresada co mo el logaritmo decimal del tiempo característico (Log t ). Estos resultados c nos muestran una disminución de la actividad ATPásica tanto con Mg + como 2+ con Ca , como consecuencia de la congelación, observando mayores pérdidas de actividad cuanto mayor es el valor de t (menor velocidad de congelación (Herring et al, 1969a;Arakawa et al, 1976;Ito et al, 1978); por otro lado, el decrecimiento de la actividad ATPásica en presencia de Ca indicaría una alteración en la estructura de miosina libre (Bodwell y Me Clain, 1976). De esto resulta, que la congelación del músculo, principalmente a velocidad len ta, está acompañada por desnaturalización de la cabeza de miosina, en la cual residen ambos sitios activos, el de la enzima (sitio de unión y de hidrólisis de ATP) y el de la interacción con actina (Ockerman, 1977;Harrington y Rodgers, 1984).…”
Section: En La Figura 5 Se Observan Los Valores Obtenidos De Actividadunclassified